Sharia Economic Dispute Resolution at the National Sharia Arbitration Board (BASYARNAS) MUI East Java: SWOT Analysis - Nadiya, Anis; Choiri, Muttaqin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the effectiveness of sharia economic dispute resolution through the National Sharia Arbitration Board (BASYARNAS) MUI East Java using SWOT analysis. Qualitative research methods with an analytical descriptive approach were used to analyze the strengths, weaknesses, opportunities, and threats of BASYARNAS in resolving sharia economic disputes. Primary data was obtained through an in-depth interview with the Chairman of Basyarnas, a Law Lecturer at Brawijaya University as well as a Notary, namely Dr. Mahdi Ahmad M.SH. M.Kn,. Meanwhile, secondary data comes from arbitration award documents and related literature. The results of the study show that BASYARNAS has strength in religious legitimacy and sharia expertise, but faces weaknesses in terms of socialization, the requirement for an arbitrator is a minimum of 15 years of experience and infrastructure. The biggest opportunity lies in the growth of the sharia economy in East Java while the main threat is competition with conventional dispute resolution institutions. The recommended strategies include increasing socialization, technology development, and improvement as well as strengthening performance in the internal scope.